Two Stay Two Stray Techniques to Improve Junior Highschool Students English Vocabulary Mastery - Bambang Nur Alamsyah Lubis; Kartina Rahmadhani Rambe; Azizah Husda (English Teaching and Linguistics Journal (ETLiJ), 2022)
This study aimed to find out the improving students English vocabulary mastery by using two stay two stray. This study was conducted by applying classroom action research in two cycles in six meetings. The population was all the seventh grade students of SMP Abdi Negara Binjai and the sample was 32. The researcher conducted the cycle I and cycle II and each cycle had vocabulary test. The number of test was 20 items. The data took from the test and analyzing by quantitative and qualitative data. The total score from the preliminary score was 2075 and the mean was 64.84 and then cycle I the total score was 22.65 and the mean was 70.78 and the cycle II the score was 2525 and the mean was 78.90 from the score, it means that two stay two stray technique could improved students vocabulary mastery.